Avaliação do risco de fratura osteoporótica por meio da ferramenta FRAX na população de idosos da cidade de Canhoba - Sergipe - Santos, Mauro Eugenio da Silva Pereira (2017)
OBJECTIVE: The objective of this study was to evaluate the risk factors for osteoporosis and osteoporotic fracture in an elderly population. METHODS: This is a descriptive, observational and cross-sectional study with a quantitative approach and convenience sampling of elderly individuals living in the city of Canhoba, municipality of Sergipe state. The data collection instrument used was a questionnaire structured and specially developed for this study that addresses demographic data, risk factors for osteoporosis and osteoporotic fracture. RESULTS: Of the 167 elderly interviewed, 133 were eligible for the study. Only 15 (11%) elderly patients reported having a diagnosis of osteoporosis, and of these, 8 (53.3%) had performed bone densitometry. In our sample, 36 (27.1%) of the elderly were supplemented with calcium and vitamin D and 3 (2.2%) used specific medications for osteoporosis. In relation to the fall of the height itself 44 (33.1%) of the elderly had fallen victims. The most frequent risk factors for osteoporosis were sedentary lifestyle (68.4%), smoking (18%), family history of osteoporosis (13.5%) and alcoholism (9.8%). Regarding the risk of fracture using the FRAX tool, we observed that the risk of hip fracture, score =3%, was 32.3% in the studied population, being (16 men and 27 women); p <0.03, whereas the risk of major osteoporotic fracture, score =20%, was 0.8%, affecting only one elderly woman. CONCLUSION: Our data demonstrate that osteoporosis is not still widely diagnosed and treated in the risk population. The FRAX tool shows to be a useful, affordable and a low cost instrument to select patients at risk of osteoporotic fractures and an appropriate treatment institution.